Composition of the Audit Committee Moderating the Whistleblowing, Corporate Governance System on Fraud - Qintharah, Yuha Nadhirah; Utami, Fransisca Listyaningsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines the effect of the whistleblowing system and good corporate governance with the audit committee as a moderating variable on fraud prevention. The population used in this study are state-owned companies listed on the Indonesia Stock Exchange for 2014-2020. The research sample was obtained by using the purposive sampling method. Analysis of the data used to use logistic regression. The number of samples used in this study was 126 for seven years of research. The results obtained show that there is an influence between whistleblowing on fraud, there is an influence between corporate governance on fraud, the composition of the audit committee is not able to moderate the relationship between whistleblowing and fraud, and also the relationship between corporate governance and fraud.